Strategi Media Relations Humas Pemerintah Kabupaten Sleman dalam Meningkatkan Citra Instansi - Bambang Sujarwadi; Dhety Chusumastuti; Aliyya Tsabita Hernindita (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This research discusses the media relations strategy of Sleman Regency Government Public Relations in improving the image of government. The Sleman Regency Government Public Relations has carried out a media relations strategy in maintaining information that is open the public, but there are still challenges in the form of newa with negative tones and delay in public relations in responding to developing issues, this has an impact on reducing the government image. This research aims to find out how the media relations strategy implemented by the Sleman Regency Government Public Relations in improving the image of the government. This research uses descriptive qualitative research methods with data collection techniques conducted throught observation, interviews, and documentation. The theoretical approach used in this research is based on the theory of media relations strategy proposed by Yosal Iriantara, namely managing relationships, developing relationship strategies, and developing networks. The result obtained show that Sleman Regency Government Public Relation has implemented Yosal Iriantara’s media relations strategy theory, by implementing three strategic processes. The fist point is managing relationship by crrying out supporting activities for media relations press conference, press tour, and press gathering, the second point is developing a relationship strategy by maintaining interpersonal communication with the media and using various media as needed in delivering information, the third process is developing networks by maintaining relationship and collaborating with professional journalist organizations. This research show that maintaining communication relationship with media partner sis very important to maintain and improve public perceptions of government.